The Clinical Spectrum of Cerebral Palsy Patients Admitted at Ayub Teaching Hospital Abbottabad - Khalid, Komal; Zahid, Masroor; Khan, Sahrish; Ali, Armaghan (Indus Journal of Bioscience Research, 2025)
Background: Cerebral palsy is a developmental condition whose manifestation results from brain damage that occurred when the child was still young; such injuries affect the limbs and other body parts as well as intellectual function. It particularly affects children below the age of 10 years and this is all over the developing nations of the world including Pakistan. The scope of the current research will be to determine the clinical manifestations and the co-morbidities in the group of CP patients from Ayub Teaching Hospital Abbottabad. Objectives: To assess the core, distribution, and quality of movement, main and secondary disabilities, as well as basic demographics and birth data, of children with CP in a hospital environment. Study Design: This is a cross-sectional study. Place and Duration of Study: The study was conducted in the Pediatrics Department of Ayub Teaching Hospital Abbottabad in the duration from 9th October, 2024 to 9th April, 2025 for six months after having been accorded approval on the synopsis. Methods: This cross-sectional study was carried on one hundred and eight cerebral palsy patients through consecutive sampling. Basic study information, past medical history, medication regimens, and comprehensive geriatric assessment were collected. Statistical processing was performed in SPSS 26; for quantitative characteristics, the mean ± SD was used; for the assessment of relationships, Chi-square/Fisher exact test were used (p < 0.05). Results: Of the 108 patient (mean age 4.5 ± 1.6 years) 60 were male. In this sample, spastic CP was identified most frequently its prevalence was 75%, epilepsy – 45%, and IDA – 30%. Hypoxic-ischemic encephalopathy which was directly contributed by birth asphyxia was closely related to the occurrence of CP (p < 0.05). Coefficient of SD for height and weight were counted ± 2.3 and ± 1.8 respectively. Conclusions: It shows that spastic cerebral palsy as the most common type and points out a range of complications, including epilepsy and intellectual disability. There are three key concepts in patient care: early interventions and utilization of interdisciplinary care. Improving on their mau on CP in high risk populations since the condition affects the neonatal period.